Determination Purchase Intention for Skincare in Indonesia - Frans Stevenardo H Silitonga; Yasintha Soelasih (Jurnal Ilmiah Manajemen dan Bisnis)
Indonesia's beauty sector has experienced substantial expansion, with an annual growth rate exceeding 4%. This corresponds with the 10% rise in national skincare product demand, underscoring an increase in consumer interest and competition in the industry. The rapid digitalization of consumer behavior has notably altered the dynamics of the skincare industry, especially in emerging markets.  This research investigates the impact of the marketing mix—product, price, place, and promotion—on consumers' purchase intentions, with electronic word of mouth (e-WOM) acting as a mediating variable.  Data were collected from 240 respondents using a purposive sampling technique. These respondents had experience purchasing skincare products online and had been exposed to e-WOM content across digital platforms.  Structural Equation Modeling (SEM) was utilized to evaluate the proposed hypotheses.  The findings demonstrate that product, price, and promotion have a significant impact on purchase intention, both directly and indirectly via e-WOM, whereas place does not show a significant direct effect.  Moreover, e-WOM plays a significant mediating role, underscoring its strategic relevance in influencing digital purchasing behavior.  The findings enhance marketing literature by merging traditional marketing strategies with mechanisms of digital consumer influence.  This study offers practical implications for skincare brands aiming to improve consumer engagement and purchase conversions via optimized marketing mix strategies and the strategic management of digital word-of-mouth channels.